Islam dan Hate Speech (Studi Fenomenologi atas Ujaran Kebencian di Indonesia) - Mujib Ridlwan; Yayuk Siti Khotijah (Al Hikmah: Jurnal Studi Keislaman, 2021)
This paper discusses the phenomenon of hated speech or hate speech which in the last five years has dominated social media in Indonesia. The state ispreoccupied with dispelling it by issuing several rules, because hate speech has exceeded the limits of reasonableness—besides cursing into the private sphere, it has also entered the realm of large organizations in the country that threaten the disintegration of the nation. This paper presents the phenomenon of hate speech in the last few years in Indonesia, then the perspective of Islam in dealing with it, as well as several solutions to overcome the proliferation of hate speech behavior. This study with a phenomenological approach to the phenomenon of hate speech in Indonesia is motivated by the threat of national disintegration due to the proliferation of hate speech behavior in Indonesia. There are three discussions, namely the phenomenon of hate speech in Indonesia, hate speech in an Islamic perspective, and the rehabilitation of hate speech addicts. Keywords: Islam, hate speech, rehabilitation.